Comparison of the Efficacy of Medical Expulsive Therapy for the Treatment of Distal Ureteric Stones with and without Mirabegron - Rajpar, Zakir Hussain; Memon, Imran Idrees; Soomro, Kashifuddin Qayoom; Hussain, Syed Azhar; Mughal, Shoukat Ali; Soomro, Naveed (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of expulsive medical therapy for treating ureteric stones with or without mirabegron as an add-on to Diclofenac. Methodology: A prospective randomized controlled trial was undertaken between April 2018 to March 2019 at the Asian Institute of Medical Sciences, Hyderabad, Sindh. A total of two hundred participants who had ureteric stones were enrolled using non-probability convenience sampling. Diclofenac Only 100 mg/day (group A, n=100), and Mirabegron 50 milligrams/day + diclofenac 100 milligrams/day (group B, n=100) were administered to patients, adjunctively. Age, sex, site, size of the stone, and laterality were noted. The stone expulsion time for each patient was evaluated. SPSS version 24 was used for analysis. A p-value of 0.05 or less was set as the cut-off value for significance. Results: Age, sex, site of stone, and laterality were not significantly different between the two groups (p=0.886, p=0.755, p=0.168, p=0.321, & p=0.889, respectively). Spontaneous stone expulsion ratios were observed as 43% and 71% in group A and group B (p<0.0001), respectively. However, no statistically significant association was found between mirabegron and the stone expulsion time (p=0.667). Group B showed a significantly higher stone expulsion rate in patients with stone size >4mm (p=0.04). The SER for middle and distally localized stones was higher in group B with a statistically significant p=0.02. Conclusion: The present study indicated that combined therapy with both mirabegron and Diclofenac is more effective than monotherapy with Diclofenac only. Mirabegron is a safe drug that improves the stone expulsion ratio in ureteric stones by > 4mm. Keywords: Mirabegron, Ureteric stone, Colic, Medical Expulsive Therapy, Efficacy, Diclofenac